A relation between the work environment and job satisfaction - Sara Lovísa Sófusdóttir 1995- (2019)
A positive relation between the work environment and job satisfaction seems to be an important factor of how employees feel about their jobs. For instance the working days can be long and people spend most part of the day at the workplace so it's important that they experience positive environment and job satisfaction. The purpose of the study was to examine what the main factors were that affects the job satisfaction. A questionnaire was sent out by email to 30 different workplaces in Iceland. The participants were 156 total, 112 women and 44 men, therefore women were 71.8% and men 28.2%. The age span ranged 18-66 years old. The results showed that there was a relation between the work environment and job satisfaction of employees. Participants working in a school had the lowest level of job satisfaction and the participants working in a service job had the highest level of job satisfaction. Between the work environment groups there was a significant difference, F (3, 143) = 5.040, p = .002. Furthermore, the results suggest that it is essential for companies to understand the importance of the social factors and a good working conditions to maximize job satisfaction at the workplace. Keywords: Job satisfaction, work environment, job burnout, gender difference Starfsánægja virðist vera mikilvægur þáttur í því hvernig starfsmönnum fyrirtækja líður með starf sitt. Vinnudagar geta verið langir og fólk ver meirihluta dagsins á vinnustaðnum og er því mikilvægt að umhverfið á vinnustaðnum sé jákvætt. Tilgangur rannsóknarinnar var að kanna hvaða meginþættir hafi áhrif á starfsánægju fólks. Spurningalisti var sendur með tölvupósti til 30 mismunandi vinnustaða á Íslandi. Þátttakendur voru 156 alls, 112 konur og 44 karlar, þar af voru konur 71,8% og karlar 28,2%. Aldur þátttakenda var á bilinu 18-66 ára. Niðurstöður rannsóknarinnar sýndu að tengsl voru á milli starfsumhverfis og starfsánægju starfsmanna. Einstaklingar sem unnu í skólum höfðu lægstu starfsánægjuna en þeir sem unnu í þjónustufyrirtæki höfðu mestu ...